International congress on ultrasonics (ICU–90) - KACZKOWSKI, Zbigniew (Archives of Acoustics, 1991)
International Congress on Ultrasonics (ICU-90) was organised by National Physical Laboratory at New Delhi on December 12-14, 1990. The congress was sponsored by the Council of Scientific and Industrial Research, Indian Council of Medical Research, Central Scientific Instrument Organisation and Ultrasonic Society of India. This was second international conference being organised by National Physical Laboratory (NPL) in ultrasonics, after the one held in July 1980. The Chairman of the Advisory Board was Prof. Dr. S. K. Joshi, Director of NPL and the Secretary was Deputy Director of NPL, Dr. V. N. Bindal. The Chairman of Organising Committee was Dr. T. K. Saksena, Co-Chairman — Mr. S. C. Gupta and Secretary — Dr. Ashok Kumar. The Convenors of the Publication and Technical Programme Committee, Finance Committee and Reception Committee were Dr. S. K. Jain, Mr. Ved Singh, Dr. J. Singh and Dr. R. P. Tandon, respectively. The Chairman of the Souvenir and Exhibition Committee was Dr. S. P. Signal and Convenior — Dr. J. N. Som.